2014
DOI: 10.1051/0004-6361/201323345
|View full text |Cite
|
Sign up to set email alerts
|

The properties of planets around giant stars

Abstract: Context. More than 50 exoplanets have been found around giant stars, revealing different properties when compared to planets orbiting solar-type stars. In particular, they are super-Jupiters and are not found orbiting interior to ∼0.5 AU. Aims. We are conducting a radial velocity study of a sample of 166 giant stars aimed at studying the population of close-in planets orbiting giant stars and how their orbital and physical properties are influenced by the post-MS evolution of the host star. Methods. We have co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 57 publications
3
89
2
Order By: Relevance
“…Radial velocity searches have found that eccentric planets are rarer around evolved hosts than around dwarfs (e.g., Jones et al 2014). However, tidal interactions are likely weak during the lifetime of HAT-P-67b; the characteristic timescale for orbital decay is on the order of~10 11 years (adopting Equation (2) of Hansen 2012 and assumes an effective stellar dissipation coefficient of  s = -10 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radial velocity searches have found that eccentric planets are rarer around evolved hosts than around dwarfs (e.g., Jones et al 2014). However, tidal interactions are likely weak during the lifetime of HAT-P-67b; the characteristic timescale for orbital decay is on the order of~10 11 years (adopting Equation (2) of Hansen 2012 and assumes an effective stellar dissipation coefficient of  s = -10 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Planets orbiting high mass stars are most likely born in high mass protoplanetary disks (e.g., Muzerolle et al 2003;Natta et al 2006), which are environments that may yield higher planet occurrence rates (e.g., Johnson et al 2010;Bowler et al 2010) and higher mass planets (e.g., Jones et al 2014;Lovis & Mayor 2007) than those around solar-type stars. Planets around early-type stars also receive a higher incident flux over their lifetimes, which in turn make them anchor-points in the planet mass-radiusequilibrium temperature relationships (e.g., Béky et al 2011;Enoch et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The KS test gives a ∼ 90% probability that both planetary mass distributions are drawn from the same population. Recently, Jones et al (2014) arrived to a different conclusion, suggesting that the mass distributions of planets around giants and subgiants are different. These authors considered all the planets around subgiants, including those with M p sin i 0.95 M Jup , which we have excluded in this analysis.…”
Section: Planetary Massmentioning
confidence: 99%
“…There is already good evidence that planetary populations around intermediate-mass stars are substantially different from those around their low-mass counterparts. Higher mass stars seem to harbor more Jupiters than do Sun-like stars , and the typical planetary mass correlates with the stellar mass (Lovis & Mayor 2007;Döllinger et al 2009;Bowler et al 2010), but there are not many planets within 1 AU of more massive stars (Johnson et al 2007;Sato et al 2008), and their orbits tend to be less eccentric than Jupiters orbiting low-mass stars (Jones et al 2014). Due to the observational difficulties associated with massive and intermediate-mass main-sequence stars, many of the more massive stars known to host planets have already reached an advanced evolutionary state, and it is not yet clear whether most of the orbital differences can be attributed to mass-dependent formation and migration, or if planetary engulfment and/or tidal evolution as the star swells on the giant branch plays a more important role.…”
Section: Introductionmentioning
confidence: 99%